I take your request to mean you want the equation solved for k.

7k + 11t = 5 - 9kt

7k + 9kt + 11t = 5 (add 9kt. This puts all of the k terms on the left.)

7k + 9kt = 5 - 11t (subtract 11t. This puts all terms not containing k on the right.)

k(7 + 9t) = 5 - 11t (factor out k)

##### k = (5 - 11t)/(7 + 9t) (divide by the coefficient of k)

7k + 11t = 5 - 9kt

7k + 9kt + 11t = 5 (add 9kt. This puts all of the k terms on the left.)

7k + 9kt = 5 - 11t (subtract 11t. This puts all terms not containing k on the right.)

k(7 + 9t) = 5 - 11t (factor out k)